Education for tomorrow's jobs - Sherman, Susan W. (National Academy Press, 1983)
The ways in which vocational education can be strengthened to contribute most effectively to national education and economic goals are the subject of this book. It discusses changes in the economy and in the nature of jobs that affect the skills needed in the workplace; unemployment conditions, particularly among the young; and the educational implications of these changes and conditions. The book takes a critical look at vocational education, evaluating the strengths and weaknesses of the system, and makes specific recommendations for its improvement.